Nanotechnology in biology and medicine : research advancements & future perspectives - Rauta, Pradipta Ranjan; Mohanta, Yugal Kishore; Nayak, Debasis (CRC Press, 2019)
"The book is focused to provide an overview on the developments made in nanotechnology till date along with the ongoing trends and the future prospects. It also present the basics, fundamental results and latest achievements in nanobiotechnological researches"--